Harhauttavat suunnittelumallit loppukäyttäjän näkökulmasta - Virtanen, Joni (2025)
Deceptive patterns can be used to guide and manipulate user behavior through different interfaces. The effectiveness of deceptive patterns is based on exploiting different heuristics and biases, through which users can be guided, forced, or misled into making decisions, that may have harmful effects on themselves, often without full understanding or consent. Deceptive patterns can lead to various harms such as loss of privacy or financial damages. Research on deceptive patterns has long focused largely on forming various taxonomies and descriptions, but the perspective and experiences of users have received less attention. This thesis uses thematic analysis to summarize how users’ experiences have been reported in current research literature. The data used in the thesis was collected using the search and selection process of systematic literature review in accordance with the PRISMA procedure. The results of the thesis show that deceptive patterns cause many different negative experiences and emotions for users. Users also seem to be unaware of the existence of such methods or their potentially negative effects. However, these negative effects are not limited to end users alone but can also turn against the actors using them. In some cases, the negative effects can also be very serious and far-reaching, such as prejudices against different groups of people.